2022
DOI: 10.3390/life12030333
|View full text |Cite
|
Sign up to set email alerts
|

EGF-Coupled Gold Nanoparticles Increase the Expression of CNPase and the Myelin-Associated Proteins MAG, MOG, and MBP in the Septal Nucleus Demyelinated by Cuprizone

Abstract: Current pharmacological therapies against demyelinating diseases are not quite satisfactory to promote remyelination. Epidermal growth factor (EGF) can expand the population of oligodendrocyte precursor cells (OPCs) that may help with the remyelination process, but its delivery into the injured tissue is still a biomedical challenge. Gold nanoparticles (GNPs) may be a useful tool for drug delivery into the brain. To evaluate remyelination in the septal nucleus, we administered intracerebral GNPs coupled with E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The latter results are remarkable as it has been demonstrated that after completed remyelination, axonal degeneration progresses at a low level, accumulating over time [ 117 ]. Notably, as some studies did not evaluate motor performance at the end of the cuprizone intoxication period [ 95 , 102 ], no conclusions can be drawn from these studies as to whether remyelination was paralleled by any functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The latter results are remarkable as it has been demonstrated that after completed remyelination, axonal degeneration progresses at a low level, accumulating over time [ 117 ]. Notably, as some studies did not evaluate motor performance at the end of the cuprizone intoxication period [ 95 , 102 ], no conclusions can be drawn from these studies as to whether remyelination was paralleled by any functional recovery.…”
Section: Discussionmentioning
confidence: 99%